Sympodiomyces attinorum sp nov., a yeast species associated with nests of the leaf-cutting ant Atta sexdens - Carreiro, S. C.; Pagnocca, F. C.; Bacci, M.; Lachance, M. A.; Bueno, O. C.; Hebling, MJA; Ruivo, CCC; Rosa, C. A. (Soc General Microbiology, 2004)
Four strains of a novel yeast species were isolated from laboratory nests of the leaf-cutting ant Atta sexdens in Brazil. Three strains were found in older sponges and one was in a waste deposit in the ant nests. Sequencing of the D1/D2 region of the large-subunit rRNA gene showed that the novel species, named Sympodiomyces attinorum sp. nov., is phylogenetically related to Sympodiomyces parvus. Unlike Sympodiomyces parvus, Sympodiomyces attinorum can ferment glucose, assimilate methyl alpha-D-glucoside, salicin and citrate, and grow at 37 degreesC, thus enabling these two species to be distinguished. Differentiation from other related species is possible on the basis of other growth characteristics. The type strain of Sympodiomyces attinorum is UNESP-S156(T) (=CBS 9734(T)=NRRL Y-27639(T)).